ANALYSIS OF THE INFLUENCE OF SOCIAL MEDIA USE ON ADOLESCENTS’ LEVELS OF EMPATHY IN THE DIGITAL AGE - Sitti Hafsah (ADISAM Publisher, 2026)
Social media has become an integral part of adolescents’ daily lives in the digital age. Whilst offering various benefits, the use of social media also raises questions regarding its impact on social and emotional development, particularly levels of empathy. This study aims to analyse the influence of social media use on adolescents’ empathy levels by examining various aspects, including social interaction, the influence of content, and gender differences. Through data collection via surveys and case studies, this research demonstrates that social media use can have both positive and negative effects on adolescents’ empathy levels, depending on how and in what context it is used. The findings of this study are expected to provide insights for parents, educators, and policymakers in understanding the social dynamics of adolescents in the digital age.